Influence of Aligned Magneto Hydrodynamic of Jeffrey Fluid across a Stretching Sheet - Al-Sharifi, H. A. M.; Abdul Rahman, Mohd Kasim; L. A., Aziz; Mohd Zuki, Salleh; S., Shafie (Informatics Publishing Limited, 2017)
Objectives: Effects of slip velocity and aligned Magneto hydro-dynamic on Jeffrey fluid which passing across a stretching sheet with Newtonian heating boundary condition are investigated. Methods/Statistical Analysis: Governing partial differential equations are first transformed into ordinary differential equation by applying the similarity transformations before undergo computation process using y bvp4c in MATLAB. Findings: For validation purposes, the present results are comparing with the outcome from previous publications for the case Constant Wall Temperature (CWT) and it shows a very strong agreement on the values of −θ′(0) . From the study, the increasing on the values of magnetic parameter, M drop the fluid velocity for the range value of boundary layer thickness 0<η<3.5. After η > 3.5 , the value of fluid velocity is increasing on the larger magnetic parameter. However, the distribution on temperature of fluid shows an opposite trend as compare with fluid velocity. On the range of 0<η<2.5, the increasing of Deborah number did not give a strong effect on the fluid velocity but at η > 2.5 it evidently reduce the velocity of fluid. The fluid temperature is high at smaller values of Deborah number. The distribution on velocity and temperature of fluid presented in this article are strictly asymptotically fulfilling the boundary conditions which then contribute to the adequate of the present results. Application/Improvements: The results from this project will enhance the knowledge in non-Newtonian fluid problem via mathematical approach.